Transperitoneal versus extraperitoneal robot‐assisted laparoscopic radical prostatectomy: A prospective single surgeon randomized comparative study. (26th July 2015) - Akand, Murat; Erdogru, Tibet; Avci, Egemen; Ates, Mutlu
<x xml:space="preserve">Abstract</x> Objectives To compare operative, pathological, and functional results of transperitoneal and extraperitoneal robot‐assisted laparoscopic radical prostatectomy carried out by a single surgeon. Methods After having experience with 32 transperitoneal laparoscopic radical prostatectomies, 317 extraperitoneal laparoscopic radical prostatectomies, 30 transperitoneal robot‐assisted laparoscopic radical prostatectomies and 10 extraperitoneal robot‐assisted laparoscopic radical prostatectomies, 120 patients with prostate cancer were enrolled in this prospective randomized study and underwent either transperitoneal or extraperitoneal robot‐assisted laparoscopic radical prostatectomy. The main outcome parameters between the two study groups were compared. Results No significant difference was found for age, body mass index, preoperative prostate‐specific antigen, clinical and pathological stage, Gleason score on biopsy and prostatectomy specimen, tumor volume, positive surgical margin, and lymph node status. Transperitoneal robot‐assisted laparoscopic radical prostatectomy had shorter trocar insertion time (16.0 vs 25.9 min for transperitoneal robot‐assisted laparoscopic radical prostatectomy and extraperitoneal robot‐assisted laparoscopic radical prostatectomy, P < 0.001), whereas extraperitoneal robot‐assisted laparoscopic radical prostatectomy had shorter console time (101.5 vs 118.3 min, respectively, P < 0.001). Total operation time and total anesthesia time were found to be shorter in extraperitoneal robot‐assisted laparoscopic radical prostatectomy, without statistical significance (200.9 vs 193.2 min; 221.8 vs 213.3 min, respectively). Estimated blood loss was found to be lower for extraperitoneal robot‐assisted laparoscopic radical prostatectomy (P = 0.001). Catheterization and hospitalization times were observed to be shorter in extraperitoneal robot‐assisted laparoscopic radical prostatectomy (7.3 vs 5.8 days and 3.1 vs 2.3 days for transperitoneal robot‐assisted laparoscopic radical prostatectomy and extraperitoneal robot‐assisted laparoscopic radical prostatectomy, respectively, P < 0.05). The time to oral diet was significantly shorter in extraperitoneal robot‐assisted laparoscopic radical prostatectomy (32.3 vs 20.1 h, P = 0.031). Functional outcomes (continence and erection) and complication rates were similar in both groups. Conclusions Extraperitoneal robot‐assisted laparoscopic radical prostatectomy seems to be a good alternative to transperitoneal robot‐assisted laparoscopic radical prostatectomy with similar operative, pathological and functional results. As the surgical field remains away from the bowel, postoperative return to normal diet and early discharge can be favored.